2015
DOI: 10.3109/01658107.2015.1039549
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcomes, Visual Fields, and Optical Coherence Tomography in Paediatric Craniopharyngioma

Abstract: Ten patients with craniopharyngioma treated for the first time when younger than 18 were included. This study reviews the visual outcomes and provides information on visual field (VF) and optical coherence tomography (OCT) examination of craniopharyngioma. The best kappa concordance coefficients between VF and OCT parameters of atrophy were obtained for the ganglion cell (GC) thickness and the mean retinal nerve fibre layer (RNFL) thickness. The agreement between GC colour maps and VF defects was good. Optic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…In contrast, Jung et al reported the mean age was 12 years [12]. There was a male preponderance in our study population, which is also consistent with other pediatric craniopharyngioma studies [8,11-13]. In contrast, Drimtzias et al and Bialer et al from the United Kingdom and Israel respectively, reported an equal ratio of males and females [6,9].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, Jung et al reported the mean age was 12 years [12]. There was a male preponderance in our study population, which is also consistent with other pediatric craniopharyngioma studies [8,11-13]. In contrast, Drimtzias et al and Bialer et al from the United Kingdom and Israel respectively, reported an equal ratio of males and females [6,9].…”
Section: Discussionsupporting
confidence: 89%
“…Improved visual outcome is the main concern for ophthalmologists and neurosurgeons managing pediatric craniopharyngioma. Table 5 summarizes published reports on visual presentation and outcome in patients with pediatric craniopharyngioma from Asian countries, the United Kingdom, Spain, Israel, and France, as well as those included in our study [6, 8-13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNFL thinning reflects irreversible retinal ganglion cell damage, which usually occurs after prolonged compression of the visual pathways. [4924] Hence, any structural damage of the retina detectable with OCT predicts the existence of irreversible injury at the optic chiasm/optic tracts that will associate visual loss to be confirmed on standard automated perimetry[11224] Despite the apparent partial visual recovery observed on our patient's initial postoperative perimetry, the OCT already reflected structural damage in the retinal ganglion cells, which had advanced with respect to the preoperative study and anticipated a long-term worsening of visual function.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, pRNFL values within normal values in patients with visual fields due to chiasmal tumours have been shown to predict visual improvement after treatment. This predictive role has been established in adults with pituitary adenoma [ 15 ] and craniopharingioma [ 16 ]. Therefore, perimetry would seem to be better than OCT evaluation of the pRNFL to detect early compression of the visual pathway in order to achieve visual improvement after treatment, both after the initial diagnosis or after recurrences.…”
Section: Discussionmentioning
confidence: 99%